2012
DOI: 10.1038/ismej.2012.9
|View full text |Cite
|
Sign up to set email alerts
|

Microbial diversity in arctic freshwaters is structured by inoculation of microbes from soils

Abstract: Microbes are transported in hydrological networks through many environments, but the nature and dynamics of underlying microbial metacommunities and the impact of downslope inoculation on patterns of microbial diversity across landscapes are unknown. Pyrosequencing of small subunit ribosomal RNA gene hypervariable regions to characterize microbial communities along a hydrological continuum in arctic tundra showed a pattern of decreasing diversity downslope, with highest species richness in soil waters and head… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

34
278
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 282 publications
(327 citation statements)
references
References 58 publications
34
278
2
1
Order By: Relevance
“…1) and it is possible that it could be influenced by exogenous eukarya transported or deposited by the snow. Similarities were observed between Sample L and a cobble-bottomed headwater stream on the North Slope of Alaska which also drains an unglaciated area underlain by continuous permafrost (Crump et al 2012). Similar to Sample L (Fig.…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…1) and it is possible that it could be influenced by exogenous eukarya transported or deposited by the snow. Similarities were observed between Sample L and a cobble-bottomed headwater stream on the North Slope of Alaska which also drains an unglaciated area underlain by continuous permafrost (Crump et al 2012). Similar to Sample L (Fig.…”
Section: Discussionsupporting
confidence: 62%
“…High abundances of Ciliophora were observed in porewater near Toolik Lake (40%, Crump et al 2012) and high relative abundances (>45%) of the superphylum Alveolata have additionally been reported in permafrost soil samples (Mackelprang et al 2011;Tveit et al 2013;Jansson and Taş 2014) and glacial meltwater (Luo et al 2009). The relative proportion of Ciliophora in a sample inferred from 18S-rRNA gene sequencing can be greater than their actual abundance since genomes can encode for multiple copies of this gene (Gong et al 2013).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Biogeography of aquatic microbial communities has been well described across spatial and seasonal scales (Gilbert et al, 2009;Galand et al, 2010;Kirchman et al, 2010;Crump et al, 2012;Fortunato et al, 2012), and although most studies discuss changes in community composition and structure, little is known about the specific taxa that distinguish one community from another. In one long-term study of the English Channel, Gilbert et al (2012) showed strong repeatable seasonal patterns in the general bacterioplankton community and in specific taxonomic groups, and found that seasonal variability was influenced by length of day, temperature, nutrients, and photosynthetically active radiation, rather than biomass of zooplankton species.…”
Section: Introductionmentioning
confidence: 99%